Prevention of Diabetic Foot Ulcers at Primary Care Level - Josephine Priyadarshini; Seham Abdi; Azza Metwaly; Badria Al-Lenjawi; Janelle San Jose; Hashim Mohamed (Dermatology, 2018)
Diabetic foot ulcer (DFT) prevention is best achieved at primary care level and should begin with education, appropriate protective footwear, glycaemic control and regular screening for loss of protective sensation. In the west, specialized diabetic or podiatry clinics may assess and quantify neuropathy with many tools including monofilaments, biothesiometry, corneal confocal microscopy and nerve conduction studies. Vascular assessment can be done via measuring ankle-brachial index, duplex ultrasound studies and toe pressure. Other foot assessment may include measuring plantar foot pressure using computerized dynamic foot studies (computerized insole sensor system). The ability to stratify patients based on risks is carried out on the basis of a thorough medical and surgical history in conjunction with these measurements thereby allowing clinicians to determine the type of intervention. Effective strategies for foot ulceration prevention include educating patients, their families, and healthcare workers about adequate foot care and regular foot examinations along with optimal glycaemic control and smoking cessation. Other effective clinical interventions may include, foot hygiene, debridement of calluses, management of foot deformities which may at times require prophylactic foot surgery. Counseling patients regarding daily proper footwear and hygiene should be stressed during each clinic visit. Educating, screening and managing patients with diabetic foot ulceration and or complications is an essential primary healthcare strategy to prevent unnecessary morbidity and mortality related to diabetic foot. An integrated (interdisciplinary) approach including, family physicians with special interest in the diabetic foot, diabetic educators, nurses and family members is a vital component in this regard.